EFSA's third Scientific Conference 'Science, Food, Society': concluding remarks. (8th July 2019) - Verhagen, Hans; Robinson, Tobin; Gallani, Barbara; Hugas, Marta; Kleiner, Juliane; Hardy, Anthony; Devos, Yann
Abstract: From 18–21 September 2018, EFSA hosted its third Scientific Conference on Science, Food and Society in Parma, Italy. This paper summarises the overall recommendations on future actions and research priorities of the conference and complements the earlier multi‐authored papers in this issue. The conference started and closed with the plenary sessions 'where science meets society: putting risk assessment in context' and 'staying relevant in a changing world', respectively. In between, there were seven breakout sessions five of which aimed at advancing risk assessment science in the areas of human health, the environment, biological hazards, nutrition and managing evidence, and two of which were dedicated to the societal aspects of risk assessment: engaging with society and envisioning the expertise of the future. During the 4 days of the event, participants addressed the complex interplay between science, risk assessment, policy and society, and explored how to advance food safety risk assessment to address the challenges of a changing world and ensure preparedness. Acknowledging that good science alone is no longer sufficient to ensure fit‐for‐purpose food safety risk assessments, EFSA must further build on its current five Strategic Objectives. To ensure that its risk assessments remain scientifically robust and sound, EFSA should strive for robust and fit‐for‐purpose risk assessments; consider food in the context of safety, nutrition and sustainability; and explore further how EFSA can work with other organisations to achieve the One Health/One Environment goals. In addition, EFSA should base scientific risk assessments on reliable science while capitalising on scientific advances; address scientific uncertainties; and fully publish the evidence and data used. In line with societal expectations, EFSA, in coordination with risk managers, should frame risk assessments through clear policy goals and problem formulation; be explicit about value judgements; communicate clearly and consistently and in coordination with risk assessors and risk managers; involve society; avoid conflicts of interest; and follow trustworthy processes.